Survey Of Basic Bolavoli Skills In Extracurricular Students At SMP Negeri 4 Kaur Regency - Fikri, Muhammad; Asnawai, Asnawati; Sumantri, Ajis (CV. Utami, 2024)
Observations made by researchers at SMP Negeri 4 Kabuapten Kaur found that during extracurricular activities in the game of volleyball there are still many students who fail to perform basic volleyball techniques such as: serving is not on target, serving out of the field even in several times serving there is a serve that does not reach the opponent's field, then there is also a passing that is not on target such as the ball is not directed to the toser, when passing the ball out of the field and there are also smashes that are not properly directed such as smash balls concerning the net, smash out of the field, smash easily blocked by the opponent. This shows that there is still a lack of mastering the basic technical skills of playing volleyball and the way students play does not meet the criteria for correct volleyball playing techniques. Therefore, the purpose of this study was to determine the level of basic skills of volleyball games in extracurricular students at SMP Negeri 4 Kaur Regency. The method used in this research is a survey research method using a quantitative descriptive approach. The population in this study amounted to 12 people, the sampling technique used total sampling technique so that the sample was 12 people. Data collection techniques using test data, secondary data and measurement scales. Data analysis was carried out descriptively quantitatively with a percentage using the survey method. The results showed that the basic technical skills of extracurricular bolavoli students at SMP Negeri 4 Kaur Regency as a whole were in the sufficient category or 66%.